Reconfigurable Assembly of Active Liquid Metal Colloidal Cluster. (28th August 2020) - Li, Zesheng; Zhang, Hongyue; Wang, Daolin; Gao, Changyong; Sun, Mengmeng; Wu, Zhiguang; He, Qiang
Abstract: We report the reconfigurable assembly of rod‐shaped eutectic gallium–indium alloy (EGaIn) liquid metal colloidal motors by mimicking the growth behavior of a dandelion. EGaIn nanorods with a diameter of 210 nm and a length of 850 nm were synthesized via an ultrasound‐assisted physical dispersion method. The nanorods possess a core–shell structure with a 30 nm GaOOH shell and zero‐valent liquid core. The EGaIn motors move autonomously at a speed of 41.2 μm s −1 under an acoustic field. By modulating the frequency of the applied acoustic field, the EGaIn colloidal motors self‐organize into various striped and circular patterns, followed by a flower‐like cluster. The dandelion‐like EGaIn colloidal motor clusters move collectively and redisperse when the applied acoustic frequency is changed. Numerical simulations reveal that the flower‐like clusters are created by the acoustic propulsion in combination with steric repulsion and hydrodynamics. Abstract : Rod‐shaped liquid metal colloidal motors were fabricated from a eutectic gallium—indium (EGaIn) alloy. On application of an acoustic field, the EGaIn colloidal motors move autonomously and they are able to self‐organize into a flower‐like cluster.